CS Indi: SU UMa-type dwarf nova with long precursor outburst. (5th November 2019) - Kato, Taichi; Hambsch, Franz-Josef; Monard, Berto; Nelson, Peter; Stubbings, Rod; Starr, Peter
Abstract: We observed the 2018 November outburst of CS Ind and confirmed that it was a genuine superoutburst with a very long [0.12471(1) d on average] superhump period. The superoutburst was preceded by a long precursor, which was recorded for the first time in SU UMa-type dwarf novae. Our interpretation is that the combination of a sufficient amount of mass in the disk before the ignition of the outburst and the slow development of tidal instability near the borderline of the 3 : 1 resonance caused a cooling front to start before the full development of tidal instability. This finding provides more support to the recent interpretation of slow development of the tidal instability causing various phenomena similar to WZ Sge-type dwarf novae in SU UMa-type dwarf novae with very long orbital periods.